2019
DOI: 10.1016/j.tranpol.2018.09.021
|View full text |Cite
|
Sign up to set email alerts
|

Port performance in container transport logistics: A multi-stakeholder perspective

Abstract: This study proposes a measurement instrument for port performance in the context of container transport logistics (CTLs) by taking perspectives from different port stakeholders. An importance-performance analysis (IPA) is used to develop an analytical tool for investigating the importance and performance (IP) of major container ports in South Korea against individual CTLs criterion. The main originality of this study is the development of a measurement instrument to provide managerial and operational insights … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(48 citation statements)
references
References 57 publications
0
45
0
3
Order By: Relevance
“…Through the analysis of the firsthand data of in-depth interviews with multimodal transport practitioners, the service quality evaluation index that conforms to the theory and practice is established [36]. From a business connection perspective, some scholars have looked at operational management by coordinating the profits between multimodal enterprises [37] and the interests among port stakeholders [38]. Considering the perspective of external risks, some scholars have focused on the impact of risk factors, climate environment, and changes in water levels [39] on intermodal transport, and helped transport networks operate smoothly through case studies.…”
Section: Container Multimodal Transportmentioning
confidence: 99%
“…Through the analysis of the firsthand data of in-depth interviews with multimodal transport practitioners, the service quality evaluation index that conforms to the theory and practice is established [36]. From a business connection perspective, some scholars have looked at operational management by coordinating the profits between multimodal enterprises [37] and the interests among port stakeholders [38]. Considering the perspective of external risks, some scholars have focused on the impact of risk factors, climate environment, and changes in water levels [39] on intermodal transport, and helped transport networks operate smoothly through case studies.…”
Section: Container Multimodal Transportmentioning
confidence: 99%
“…An overlay network [16] is the most commonly used container network on multiple nodes. An overlay network configuration is needed to allow containers to communicate with each other on multiple nodes [17][18][19]. Representative overlay networking solutions for containers are divided into two catagories: linux bridge overlay network and Flannel networking.…”
Section: Container Networking On Multiple Nodesmentioning
confidence: 99%
“…Further, they focused on several factors that may influence container exchange among carriers. Ha et al [45] suggested a measurement instrument for port performance in the context of container transport logistics by taking perspectives from different port stakeholders.…”
Section: Literature Reviewmentioning
confidence: 99%